(untitled) (Global Journal of Medical Research, 2014)
Introduction-The conventional method of diagnosing ascariasis is by testing the stool for the presence of the eggs. When there are atypical abdominal symptoms a routine ultrasound scan using the common 3-3.5 MHz probe yields no definite findings to diagnose intestinal ascariasis. If a high frequency probe of 5-10 MHz is used instead, intestinal ascariasis could be definitely established. This case illustrates a typical worm diagn-osed with the help of a high frequency probe.